Analisis Potensi Penerimaan Pajak Restoran di Kota Bekasi - Harjo, Dwikora; Rahmawati, Aninda; Milleano, Dani (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research is motivated by the failure to achieve the target and actual revenue from restaurant taxes in Bekasi City over the past three years, namely 2020, 2021, and 2022, with a decreasing trend. Restaurant taxes are one of the sources of local tax revenue used for the benefit of the local area. The local government must optimize the exploration of potential revenue from restaurant taxes. The purpose of this research is to analyze the potential revenue from restaurant taxes in Bekasi City Regional Revenue Agency in generating local tax revenue sourced from restaurant taxes. The theory used in this research is the potential theory according to Kenneth Davey. This study adopts a qualitative descriptive approach. The data used in this research consist of primary data obtained from interviews and secondary data obtained from observations and documentation. The results of this research indicate that the potential revenue from restaurant taxes in Bekasi City is substantial, based on the potential calculation and recapitulation of potential revenue from restaurant taxes in. Bekasi City for the years 2020 amounted to 397,992,901,224 IDR, 2021 amounted to 449.111.255.510 IDR, and 2022 amounted to 472, 130,390,204 IDR.